Cross cultural adaptation and validation of audiovisual educational material for use in indigenous patients with rheumatoid arthritis - Joana Aguilar-Castillo; Ingris Peláez-Ballestas; José-Luis Montiel-Hernández; Cairo Toledano-Jaimes; Mario-Alberto Garza-Elizondo; David Zepeda-González; Diana-Lizbeth Gómez-Galicia (PEC Innovation)
Background: Culturally appropriate educational materials are necessary to improve health literacy among Indigenous populations. However, practically no such materials have been cross-culturally adapted and validated for Indigenous peoples based on compliance with efficacy components. Objective: To perform a cross-cultural adaptation and validation of audiovisual educational materials for adult patients with rheumatoid arthritis belonging to Indigenous communities in Chiapas, Mexico. Methods: Mixed-methods study consisting of three phases: 1) Spanish–Tzotzil translation and cross-cultural adaptation of seven previously designed and validated audiovisual educational materials; 2) qualitative validation; and 3) quantitative validation based on the efficacy components (attraction, understanding, induction to action, involvement, and acceptance). The information collected during the validation phases was recorded and transcribed for content analysis. Results: A total of 31 patients with rheumatoid arthritis participated in the study. Patients had a mean age of 49 years, ≥5 years since disease onset, low adherence to pharmacological treatment (<20%), and a high level of illiteracy (>80%). After three versions of the educational material, where elements of cultural identification were added, the efficacy components increased significantly to reach scores higher than 90%. This suggests that culturally-adapted materials could promote greater patient participation in treatment. Conclusion: This study shows the importance of cross-cultural adaptation in the design and validation of audiovisual educational materials for Indigenous populations; this aspect should be considered when implementing educational strategies for patients with chronic diseases. Innovation: First educational audiovisual material translated and adapted from Spanish to Tzotzil, with a cultural sensitivity approach to achieve educational goals and improve therapeutic adherence.